2012
DOI: 10.1016/j.neuro.2012.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Sex and rearing condition modify the effects of perinatal lead exposure on learning and memory

Abstract: Developmental lead (Pb) exposure is associated with cognitive impairments in humans and rodents alike. In particular, impaired spatial learning and memory, as assessed using the Morris water maze (MWM), has been noted in developmentally Pb –exposed rats. Although sex and rearing environment can influence MWM performance in normal animals, the interactions of sex and rearing environment on the impact of developmental Pb exposure on hippocampal-dependent processes has not been well characterized. The present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 70 publications
4
26
0
Order By: Relevance
“…We and others have previously reported sex-related differences in hippocampus-based learning and memory (Anderson et al, 2012), gene expression patterns in both the frontal cortex and hippocampus of littermates (Anderson et al, 2013; Schneider et al, 2011) and modulation of epigenetic control elements including DNA methyltransferases of littermates (Schneider et al, 2013) following Pb-exposure. The results of the current study suggest that there are also complex effects of sex, developmental window of exposure and level of Pb-exposure on associative memory as assessed by trace fear conditioning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We and others have previously reported sex-related differences in hippocampus-based learning and memory (Anderson et al, 2012), gene expression patterns in both the frontal cortex and hippocampus of littermates (Anderson et al, 2013; Schneider et al, 2011) and modulation of epigenetic control elements including DNA methyltransferases of littermates (Schneider et al, 2013) following Pb-exposure. The results of the current study suggest that there are also complex effects of sex, developmental window of exposure and level of Pb-exposure on associative memory as assessed by trace fear conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…The cognitive/behavioral effects of Pb exposure have been modeled in numerous animal studies, with the majority of studies focusing on hippocampal-associated spatial learning and memory processes in rodents, most often using the Morris water maze (ex., (Jett et al, 1997; Toscano and Guilarte, 2005). Although these studies have provided useful information on the effects of Pb on hippocampus-associated learning and memory, the water maze task may not be optimal for detecting more subtle behavioral disturbances as might occur with lower level exposures to Pb (Anderson et al, 2012; Jett et al, 1997). Other studies have examined the effects of low level developmental Pb exposures (i.e., blood Pb levels < 10μg/dl) on frontal cortex-associated attention and impulsivity problems using fixed-interval/fixed ratio testing or performance on a delay discounting task (Brockel and Cory-Slechta, 1998; Weston et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors concluded that the environmental manipulation was a potential risk modifier of developmental Pb exposure. Furthermore, the authors stated that sex and amount of Pb exposure affected the functional influence of Pb on brain [33]. Thus, results of human and animal studies have reported conflicting results in terms of short-and long-term memory.…”
Section: Spatial Learning and Memorymentioning
confidence: 99%